Editorial - Martha Cleveland-Innes (The Canadian Network for Innovation in Education (CNIE), 2023)
This next Canadian Journal of Learning and Technology issue is published on the heels of the well-attended ICDE (International Council for Open and Distance Education) conference. The Conference's overlapping topics and attendant researchers, well-known to this journal, remind us that our field is important, well-subscribed, growing, and changing. An excellent overview of this ICDE Conference and information about the state of education transformation in the current global context can be found here in recent blog posts by the well-known expert and author on the topic of education and technology, Dr. Tony Bates. Learning and technology, the focus of research published by CJLT, is a microcosm in the much larger fields of open, distance, and digital education. Research spans all sectors: primary, secondary, post-secondary, higher education, and lifelong learning. Across issues and years, we seek to touch on the research, theory, and practice in these areas, particularly those where authors are in, or research topics are relevant to, Canada. Canadian researchers were well-represented at the recent ICDE conference, and a Canadian researcher received the conference's best paper award!